Extended citizenship. Laws and activism from the civil society (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
In this article we intend to record and analyze the process developed in the province of La Pampa for the obtaining of the law that guarantees ligation tubal and vasectomy in the State health services, sanctioned by the end of 2003. It is not a specific law, but that practice was included in other legislation. This process was led by a group that emerged, was strengthened and forged its identity from this activism. Also, we will realize the treatment of the law in the legislature of La Pampa.
Keywords: Sexual and reproductive right; women movemen; citizenship.